A polyester / silk composite vascular stent coating with bionic interface and preparation method thereof

By using polyester braided composite silk fibroin in vascular stent coating, the problem of prone to complications in existing vascular stent coating is solved, and the effects of rapid endothelialization and long-term patency are achieved.

CN116407690BActive Publication Date: 2025-02-25SUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310282015.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-02-25
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

The existing vascular stent coating is prone to complications such as stent displacement, endospermia, thrombosis and restenosis after surgery, and it is difficult to achieve endothelialization, resulting in technical problems of unsatisfactory intervention.

Method used

The vascular stent covering the composite regenerated silk fibroin with polyester braided fabric. The inner layer is composed of silk fibroin nanofibers prepared by electrospinning. The outer layer forms polyester tubular fabric through braiding technology and performs multiple solutions in the silk fibroin mixed solution. Sub-immersion and rotational film formation to form a coating with a bionic vascular endometrial interface.

Benefits of technology

A vascular stent that rapidly induces endothelialization, prevents thrombosis, maintains blood flow homeostasis, and has long-term patency, significantly improves cell adhesion, proliferation, and NO release, and enhances biological activity and histocompatibility.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a polyester / silk composite vascular stent coating with a bionic interface and a preparation method thereof, comprising the following steps: (1) spinning silk nanofibers on the surface of a core rod by electrospinning technology, and then quickly dipping them in a modified silk fibroin mixed solution mixed with a flexible cross-linking agent, and then rotating and drying and repeating this step several times to form an inner layer of the vascular stent coating; (2) weaving a polyester tubular fabric on the basis of the inner layer of the stent coating by weaving technology to form a core layer of the vascular stent coating; (3) dipping the core layer of the stent coating in a modified silk fibroin mixed solution mixed with a flexible cross-linking agent, rotating and drying and repeating this step several times to form a vascular stent coating with layers of tight connection, and finally immersing the nanofibers in deionized water to dissolve the nanofibers to form a coating inner surface with a tightly connected flat island-shaped microscopic morphology, thereby obtaining a polyester / silk composite vascular stent coating with a bionic vascular endothelial interface that can quickly induce endothelialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials, relates to the preparation of a vascular stent coating, and specifically relates to a vascular stent coating of a polyester braided fabric composite with regenerated silk fibroin having a bionic vascular endothelial interface and a preparation method thereof. Background Art

[0002] The incidence, morbidity and mortality of cardiovascular and cerebrovascular diseases have been increasing year by year. Atherosclerosis is the main cause of such diseases, which begins with intimal stimulation such as lipid or sugar accumulation, leading to thickening, hardening and narrowing of the arterial wall, and eventually deteriorating into occlusive arterial disease (including coronary heart disease, cerebral infarction and peripheral vascular disease).

[0003] At present, more and more covered stents are used clinically to treat vascular obstruction. The commonly used covered materials of commercial covered stents are mainly polyester and polytetrafluoroethylene. Although these two synthetic materials have excellent mechanical properties, they have defects such as poor compliance and biological inertness. It is difficult to achieve endothelialization after implantation in the body, which is the main cause of postoperative complications. Especially for the middle-aged and elderly population, not only is the incidence of thrombosis high, but the ability of their own tissue regeneration is weak. Therefore, higher requirements are placed on the biological activity of the inner surface of this type of synthetic polymer stent coating - after implantation, it is hoped that rapid endothelialization can be achieved while maintaining long-term mechanical support, fundamentally inhibiting the occurrence of thrombosis and inflammation.

[0004] Silk fibroin is a natural protein derived from animals, composed of 20 kinds of amino acids, and has the same components as the extracellular matrix. Existing literature studies have shown that artificial blood vessels constructed with silk fibroin can support the adhesion, growth and proliferation of vascular cells, induce endothelialization after implantation in the body, maintain smooth blood flow, and induce the regeneration of vascular tissue in situ. It has received great attention in the field of vascular tissue engineering materials. Based on its good blood compatibility, it is also a preferred material for surface modification of synthetic polymers such as polyester or polytetrafluoroethylene coatings in existing clinical applications.

[0005] In view of the fact that the current covered stents are still prone to complications such as stent migration, endoleak, thrombosis and restenosis in the mid- and long-term after surgery, which leads to a high proportion of unsatisfactory interventions, it is necessary to develop an active stent covering with a bionic vascular microstructure to solve the above problems. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention aims to solve the technical problems and provide a vascular stent coating of polyester woven fabric composited with regenerated silk fibroin with a bionic vascular endothelial interface and a preparation method thereof, which is used to produce a vascular stent that can quickly induce endothelialization, prevent thrombosis, maintain blood flow homeostasis, and maintain long-term patency.

[0007] The present invention provides a vascular stent coating of polyester braided fabric composite regenerated silk fibroin with a bionic vascular endothelial interface and a preparation method thereof, wherein the inner surface of the coating is designed while adjusting its microstructure, thereby giving the coating good mechanical properties and excellent biological activity.

[0008] In order to achieve the above technical objectives, the specific steps adopted by the present invention are as follows:

[0009] (1) degumming silkworm silk with boiling water, sodium carbonate, sodium bicarbonate or biological enzymes to obtain silk fibroin (hereinafter referred to as silk fibroin) fibers, and then completely dissolving the fibers in a lithium bromide solution to obtain a silk fibroin solution; pouring the silk fibroin solution into a dialysis bag, dialyzing the solution with deionized water, filtering the solution to obtain a purified silk fibroin protein aqueous solution, and evaporating and concentrating the solution to adjust the concentration of the silk fibroin protein aqueous solution to 10 to 200 mg / mL;

[0010] (2) placing the polyester yarn in a sodium carbonate solution for a period of time, washing it with deionized water, completing the degreasing and desizing treatment, repeating the degreasing and desizing treatment several times, and finally obtaining the pretreated polyester yarn; placing the pretreated polyester yarn in a sodium hydroxide solution for surface activation treatment, and washing it with deionized water after the surface activation treatment to obtain the alkali-treated polyester yarn;

[0011] (3) Preparation of the inner layer of the stent coating;

[0012] (a) using a silk fibroin aqueous solution as an electrospinning solution, spinning silk fibroin nanofibers on a cylindrical auxiliary rod by electrospinning to obtain an auxiliary rod with silk fibroin nanofibers; the concentration of the silk fibroin aqueous solution is 50 to 180 mg / mL, the average diameter of the silk fibroin nanofibers is 100 to 5000 nm, and the average orientation degree of the silk fibroin nanofibers is 30 to 90%;

[0013] (b) adding a hydrophilic and flexible cross-linking agent to a silk fibroin aqueous solution to obtain a modified silk fibroin mixed solution; then dipping an auxiliary rod with silk fibroin nanofibers in the modified silk fibroin mixed solution, taking it out after dipping and placing it in an environment of 20 to 50° C. for rotation to form a film, completing an immersion treatment; repeating the immersion treatment several times to form an inner layer of the stent coating; the silk fibroin concentration in the modified silk fibroin mixed solution is 30 to 100 mg / mL;

[0014] (4) weaving the polyester yarn treated with alkali in step (2) on the outer surface of the inner layer of the stent coating in step (3) to form a polyester tubular fabric with a weaving angle of 30 to 150 degrees and an axial weaving density of 1 to 20 strands / cm to form a core layer of the vascular stent coating;

[0015] (5) Soaking the core layer of the vascular stent coating of step (4) in the modified silk fibroin mixed solution of step (3), taking it out after soaking and placing it in an environment of 20 to 50° C. for rotation to form a film, thus completing one soaking treatment; repeating the soaking treatment several times to obtain the vascular stent coating; finally, soaking the vascular stent coating in sterile deionized water to remove unreacted cross-linking agent and silk fibroin molecules and dissolving silk fibroin nanofibers to obtain a polyester / silk fibroin composite vascular stent coating with a bionic interface.

[0016] Preferably, the concentration of the lithium bromide solution in step (1) is 9.3 M; the dialysis bag is a semipermeable membrane with a molecular weight cutoff of 3 to 50 kDa, and the dialysis is performed with deionized water for 3 days.

[0017] Preferably, the mass concentration of the sodium carbonate solution in step (2) is 1%, the temperature of the desizing treatment is 95-100° C., and the treatment time is 2 hours; the number of treatments is 2-5 times; the concentration of the sodium hydroxide solution is 20-50 g / L, the surface activation treatment temperature is 30-80° C., and the treatment time is 1-3 hours.

[0018] Preferably, the cylindrical auxiliary rod in step (3) (a)-(b) is a stainless steel rod with a diameter of 1 to 30 mm;

[0019] Preferably, the rotation speed of the cylindrical auxiliary rod during electrospinning in step (3) (a) is 100 to 3000 rpm.

[0020] Preferably, in step (3) (b), the mass ratio of silk fibroin to cross-linking agent is 1.0:(0.3-1.0), the cross-linking agent is polyethylene glycol diglycidyl ether, the immersion time in the modified silk fibroin mixed solution is 10-60 seconds, the immersion treatment is repeated 0-5 times, the rotation speed during rotational film formation is 20-80 rpm, and the rotation direction is along the circumference of the auxiliary rod.

[0021] Preferably, the polyester yarn in step (4) is any one of polyester monofilament and polyester multifilament, with a specification of 5 to 200D.

[0022] Preferably, in step (5), the immersion time in the modified silk fibroin mixed solution is 10 to 60 seconds, the rotation speed during the rotational film formation is 20 to 80 rpm, the rotation direction is along the circumference of the auxiliary rod, and the time is 10 to 30 minutes; the repeated immersion treatment is repeated 2 to 10 times.

[0023] Preferably, the temperature of the sterile deionized water in step (5) is 4 to 37° C., and the soaking time is 1 to 3 days.

[0024] Beneficial effects:

[0025] The technical solution and creativity of the present invention lies in that the prepared vascular stent coating has excellent endothelialization promoting function, which fundamentally solves the problem that the polyester or polytetrafluoroethylene vascular stents used in clinical practice cannot be endothelialized and are still prone to thrombosis after surgery.

[0026] The polyester / silk composite vascular stent coating provided by the present invention has good performance, axial tensile strength of 12.0MPa, elongation at break of 120%, circumferential tensile strength of 6.0MPa, elongation at break of 50%, water bursting strength of 3500mmHg, compliance of 10.0% / 100mmHg, and overall water leakage of less than 10mL / min.cm under 120mmHg water pressure 2 , hemolysis rate <0.1%.

[0027] The vascular stent coating prepared by the present invention has excellent endothelialization promoting function. Taking Example 3 as an example, after endothelial cells were cultured on its surface for 3 days, the cell adhesion rate on the polyester / silk composite vascular stent coating of the present invention increased by 94% compared with that in control Example 4, the cell proliferation rate increased by 90% compared with that in control Example 4, and the endothelial cell NO release increased by 80% compared with that in control Example 4.

[0028] The silk fibroin layer of the polyester / silk fibroin composite vascular stent coating provided by the present invention has ideal biological activity, and can especially well support the growth of vascular endothelial cells, and the negatively charged inner surface prevents the adhesion of proteins and blood cells in plasma; the silk fibroin composited on the inner and outer surfaces of the polyester braided fabric enables it to form ideal tissue compatibility with the autologous vascular tissue after implantation, and the core layer and the outer layer are tightly connected and closely fit to the vascular lesion site, and will not be inconsistent or slip due to the incompatibility of materials and mechanical properties.

[0029] The innovation of the present invention lies in that the inner surface of the silk protein constructed in the stent coating dissolves a tightly connected flat island-shaped nanometer-scale groove, which has a microscopic topological structure that highly imitates the natural vascular endothelial layer, and is more conducive to the homing and proliferation of endothelial (progenitor) cells. Promoting the homing of endothelial (progenitor) cells and rapid endothelialization is a fundamental strategy to permanently inhibit implants from inducing thrombosis and restenosis again. The newly formed complete endothelial layer can effectively maintain the balance of blood coagulation and keep it unobstructed for a long time. The topological structure of the bionic nanometer-scale groove on the inner surface of the stent coating has adjustable groove size, directionality and orderliness, which not only solves the problem of preventing thrombosis and restenosis, but also can reduce blood flow rate, maintain blood flow homeostasis and buffer high-pressure blood flow. After the stent coating provided by the present invention is implanted, with the rapid formation of endothelialization and the gradual degradation and absorption of the silk film layer, the intimal tissue of the autologous blood vessel is finally reproduced in situ, and is closely connected to the middle membrane tissue through the woven mesh. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described in the present invention are only for describing specific embodiments and are not intended to limit the present invention. It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments obtained from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0032] Embodiment 1:

[0033] (1) Place the silkworm silk in a sodium carbonate aqueous solution with a mass concentration of 0.1% at a bath ratio of 1:50 g / mL, treat it at a temperature of 98-100°C for three times, each time for 30 minutes, then wash it thoroughly with deionized water, and place it in a 60°C oven to dry for 12 hours to obtain degummed silk fibers. Weigh the degummed silk fibers and completely dissolve them in a 9.3M lithium bromide solution at a bath ratio of 1:10 g / mL in a 65±5°C water bath environment to obtain a silk fibroin solution;

[0034] The silk fibroin solution was poured into a dialysis bag (molecular weight cut-off: 14 kDa), and dialyzed with deionized water for 3 days to obtain a purified silk fibroin aqueous solution. The purified silk fibroin aqueous solution was concentrated and adjusted to a desired concentration.

[0035] (2) placing the polyester yarn in a sodium carbonate solution with a mass concentration of 1% at a bath ratio of 1:50 g / mL, treating it at a temperature of 98-100° C. for three times, each time for 2 hours, and then washing it thoroughly with deionized water to obtain the pretreated polyester yarn; placing the pretreated polyester yarn in a 20 g / L sodium hydroxide aqueous solution at a bath ratio of 1:50 g / mL for surface activation treatment, the surface activation treatment temperature is 35±5° C., the treatment time is 1 hour, and then washing it with deionized water to obtain the alkali-treated polyester yarn.

[0036] (3) Using 50 mg / mL silk fibroin aqueous solution as the electrospinning solution, electrospinning silk fibroin nanofibers on a stainless steel rod (10 mm in diameter) at a rotation speed of 1500 rpm by electrospinning, the average diameter of the silk fibroin nanofibers was 200±80 nm, and the average orientation degree was 50±15%, obtaining a stainless steel rod wound with silk fibroin nanofibers;

[0037] The stainless steel rod wrapped with silk nanofibers was then immersed in a modified silk fibroin mixed solution containing a hydrophilic and flexible cross-linking agent, the mass ratio of silk fibroin to cross-linking agent being 1:0.5, the cross-linking agent being polyethylene glycol diglycidyl ether, and the silk fibroin concentration in the modified silk fibroin mixed solution being 60 mg / mL. The rod was immersed for 60 seconds, taken out and placed at 35°C and rotated in a circular direction to form a film at a rotation speed of 60 rpm to form the inner layer of the stent coating.

[0038] (4) The alkali-treated polyester yarn is woven into a polyester tubular fabric with a weaving angle of 120° and an axial weaving density of 4 strands / cm on the outer surface of the inner layer of the stent coating by using a weaving technique to form a core layer of the vascular stent coating.

[0039] (5) Immersing the core layer of the stent coating of the above step (4) in the modified silk fibroin mixed solution containing the crosslinking agent in the above step (3) for 60 seconds, taking it out and placing it in a 35°C environment and rotating it in a circular direction to form a film at a rotation speed of 60 rpm to complete one immersion treatment; and controlling the surface of the film to remain moist, repeating the immersion treatment 6 times to form the outer layer of the stent coating, thereby obtaining the stent coating, and finally immersing the stent coating in 37°C sterile deionized water for 1 day to remove the unreacted crosslinking agent and silk fibroin molecules and dissolve the silk fibroin nanofibers to obtain a polyester / silk fibroin composite stent coating with a bionic interface.

[0040] After testing, the above-mentioned polyester / silk composite vascular stent coating with a bionic interface has excellent endothelialization-promoting ability. After endothelial cells were cultured on its surface for 3 days, the cell adhesion rate on the polyester / silk composite vascular stent coating of the present invention increased by 59% compared with that in control example 4, the cell proliferation rate increased by 48% compared with that in control example 4, and the endothelial cell NO release increased by 42% compared with that in control example 4.

[0041] Embodiment 2:

[0042] (1) Place the silkworm silk in a sodium carbonate aqueous solution with a mass concentration of 0.1% at a bath ratio of 1:50 g / mL, treat it at a temperature of 98-100°C for three times, each time for 30 minutes, then wash it thoroughly with deionized water, and place it in a 60°C oven to dry for 12 hours to obtain degummed silk fibers. Weigh the degummed silk fibers and completely dissolve them in a 9.3M lithium bromide solution at a bath ratio of 1:10 g / mL in a 65±5°C water bath environment to obtain a silk fibroin solution;

[0043] The silk fibroin solution was poured into a dialysis bag (molecular weight cut-off: 14 kDa), and dialyzed with deionized water for 3 days to obtain a purified silk fibroin aqueous solution. The purified silk fibroin aqueous solution was concentrated and adjusted to a desired concentration.

[0044] (2) The polyester yarn is placed in a sodium carbonate solution with a mass concentration of 1% at a bath ratio of 1:50 g / mL, and treated at a temperature of 98-100° C. for three times, each time for 2 hours, and then fully washed with deionized water to obtain pretreated polyester yarn. The pretreated polyester yarn is placed in a 20 g / L sodium hydroxide aqueous solution at a bath ratio of 1:50 g / mL for surface activation treatment, the surface activation treatment temperature is 35±5° C., the treatment time is 1 hour, and then washed with deionized water to obtain alkali-treated polyester yarn.

[0045] (3) Using 140 mg / mL silk fibroin aqueous solution as the electrospinning solution, electrospinning silk nanofibers on a stainless steel rod (diameter 10 mm) rotating at a speed of 1500 rpm by electrospinning, the average diameter of the silk nanofibers is 700±150 nm, and the average orientation degree is 50±18%, thereby obtaining a stainless steel rod wound with silk nanofibers; then, the stainless steel rod wound with silk nanofibers is immersed in a modified silk fibroin mixed solution containing a hydrophilic and flexible cross-linking agent, the mass ratio of silk fibroin to cross-linking agent is 1:0.5, the cross-linking agent is polyethylene glycol diglycidyl ether, and the silk fibroin concentration in the silk fibroin mixed solution is 60 mg / mL. The mixture is immersed for 60 seconds, and the mixture is taken out and placed in a 35°C environment and rotated in a circular direction to form a film at a rotation speed of 60 rpm to form the inner layer of the stent coating.

[0046] (4) The alkali-treated polyester yarn is woven into a polyester tubular fabric with a weaving angle of 120° and an axial weaving density of 4 strands / cm on the outer surface of the inner layer of the stent coating by using a weaving technique to form a core layer of the vascular stent coating.

[0047] (5) Immersing the core layer of the stent coating of the above step (4) in the modified silk fibroin mixed solution containing the crosslinking agent in the above step (3) for 60 seconds, taking it out and placing it in a 35°C environment and rotating it in a circular direction to form a film at a rotation speed of 60 rpm to complete one immersion treatment; and controlling the surface of the film to remain moist, repeating the immersion treatment 6 times to form the outer layer of the stent coating, thereby obtaining the stent coating, and finally immersing the stent coating in 37°C sterile deionized water for 1 day to remove the unreacted crosslinking agent and silk fibroin molecules and dissolve the silk fibroin nanofibers to obtain a polyester / silk fibroin composite stent coating with a bionic interface.

[0048] After testing, the above-mentioned polyester / silk composite vascular stent coating with a bionic interface has excellent endothelialization-promoting ability. After endothelial cells were cultured on its surface for 3 days, the cell adhesion rate on the polyester / silk composite vascular stent coating of the present invention increased by 75% compared with that in control example 4, the cell proliferation rate increased by 69% compared with that in control example 4, and the endothelial cell NO release increased by 61% compared with that in control example 4.

[0049] Embodiment 3:

[0050] (1) Place the silkworm silk in a sodium carbonate aqueous solution with a mass concentration of 0.1% at a bath ratio of 1:50 g / mL, treat it at a temperature of 98-100°C for three times, each time for 30 minutes, then wash it thoroughly with deionized water, and place it in a 60°C oven to dry for 12 hours to obtain degummed silk fibers. Weigh the degummed silk fibers and completely dissolve them in a 9.3M lithium bromide solution at a bath ratio of 1:10 g / mL in a 65±5°C water bath environment to obtain a silk fibroin solution;

[0051] The silk fibroin solution was poured into a dialysis bag (molecular weight cut-off: 14 kDa), and dialyzed with deionized water for 3 days to obtain a purified silk fibroin aqueous solution. The purified silk fibroin aqueous solution was concentrated and adjusted to a desired concentration.

[0052] (2) placing the polyester yarn in a sodium carbonate solution with a mass concentration of 1% at a bath ratio of 1:50 g / mL, treating it at a temperature of 98-100° C. for three times, each time for 2 hours, and then washing it thoroughly with deionized water to obtain the pretreated polyester yarn; placing the pretreated polyester yarn in a 20 g / L sodium hydroxide aqueous solution at a bath ratio of 1:50 g / mL for surface activation treatment, the surface activation treatment temperature is 35±5° C., the treatment time is 1 hour, and then washing it with deionized water to obtain the alkali-treated polyester yarn.

[0053] (3) Using 140 mg / mL silk fibroin aqueous solution as the electrospinning solution, electrospinning silk nanofibers on a stainless steel rod (diameter 1-30 mm) rotating at a speed of 3000 rpm by electrospinning, the average diameter of the silk nanofibers is 700±150 nm, and the average orientation degree is 80±10%, thereby obtaining a stainless steel rod wound with silk nanofibers; then, the stainless steel rod wound with silk nanofibers is immersed in a modified silk fibroin mixed solution containing a hydrophilic and flexible cross-linking agent, the mass ratio of silk fibroin to cross-linking agent is 1:0.5, the cross-linking agent is polyethylene glycol diglycidyl ether, and the silk fibroin concentration in the silk fibroin mixed solution is 60 mg / mL. The mixture is immersed for 60 seconds, and the mixture is taken out and placed in a 35°C environment and rotated in a circular direction to form a film at a rotation speed of 60 rpm to form the inner layer of the stent coating.

[0054] (4) The alkali-treated polyester yarn is woven into a polyester tubular fabric with a weaving angle of 120° and an axial weaving density of 4 strands / cm on the outer surface of the inner layer of the stent coating by using a weaving technique to form a core layer of the vascular stent coating.

[0055] (5) Immersing the core layer of the stent coating of the above step (4) in the modified silk fibroin mixed solution containing the crosslinking agent in the above step (3) for 60 seconds, taking it out and placing it in a 35°C environment and rotating it in a circular direction to form a film at a rotation speed of 60 rpm to complete one immersion treatment; and controlling the surface of the film to remain moist, repeating the immersion treatment 6 times to form the outer layer of the stent coating, thereby obtaining the stent coating, and finally immersing the stent coating in 37°C sterile deionized water for 1 day to remove the unreacted crosslinking agent and silk fibroin molecules and dissolve the silk fibroin nanofibers to obtain a polyester / silk fibroin composite stent coating with a bionic interface.

[0056] After testing, the above-mentioned polyester / silk composite vascular stent coating with a bionic interface has excellent endothelialization-promoting ability. After endothelial cells were cultured on its surface for 3 days, the cell adhesion rate on the polyester / silk composite vascular stent coating of the present invention increased by 94% compared with that in control example 4, the cell proliferation rate increased by 90% compared with that in control example 4, and the endothelial cell NO release increased by 80% compared with that in control example 4.

[0057] The polyester / silk composite vascular stent coating with bionic interface has excellent mechanical properties. The inner surface of the coating has an axial tensile strength of 12.0 MPa and a breaking elongation of 120% according to the national standard testing method. The circumferential tensile strength is 6.0 MPa and the breaking elongation is 50%. The water bursting strength is 3500 mmHg, the compliance is 10.0% / 100 mmHg, and the overall water leakage is less than 10 mL / min.cm under a water pressure of 120 mmHg. 2 , hemolysis rate <0.1%.

[0058] Embodiment 4 (comparative example):

[0059] (1) Place the silkworm silk in a sodium carbonate aqueous solution with a mass concentration of 0.1% at a bath ratio of 1:50 g / mL, treat it at a temperature of 98-100°C for three times, each time for 30 minutes, then wash it thoroughly with deionized water, and place it in a 60°C oven to dry for 12 hours to obtain degummed silk fibers. Weigh the degummed silk fibers and completely dissolve them in a 9.3M lithium bromide solution at a bath ratio of 1:10 g / mL in a 65±5°C water bath environment to obtain a silk fibroin solution;

[0060] The silk fibroin solution was poured into a dialysis bag (molecular weight cut-off: 14 kDa), and dialyzed with deionized water for 3 days to obtain a purified silk fibroin aqueous solution. The purified silk fibroin aqueous solution was concentrated and adjusted to a desired concentration.

[0061] (2) placing the polyester yarn in a sodium carbonate solution with a mass concentration of 1% at a bath ratio of 1:50 g / mL, treating it at a temperature of 98-100° C. for three times, each time for 2 hours, and then washing it thoroughly with deionized water to obtain the pretreated polyester yarn; placing the pretreated polyester yarn in a 20 g / L sodium hydroxide aqueous solution at a bath ratio of 1:50 g / mL for surface activation treatment, the surface activation treatment temperature is 35±5° C., the treatment time is 1 hour, and then washing it with deionized water to obtain the alkali-treated polyester yarn.

[0062] (3) A stainless steel rod (10 mm in diameter) was immersed in a modified silk fibroin mixed solution containing a hydrophilic and flexible cross-linking agent, the mass ratio of silk fibroin to cross-linking agent being 1:0.5, the cross-linking agent being polyethylene glycol diglycidyl ether, and the silk fibroin concentration in the silk fibroin mixed solution being 60 mg / mL. The rod was immersed for 60 seconds, taken out and placed at 35°C and rotated in a circular direction to form a film at a rotation speed of 60 rpm to form the inner layer of the stent coating.

[0063] (4) The alkali-treated polyester yarn is woven into a polyester tubular fabric with a weaving angle of 120° and an axial weaving density of 4 strands / cm on the outer surface of the inner layer of the stent coating by using a weaving technique to form a core layer of the vascular stent coating.

[0064] (5) Immersing the core layer of the stent coating of the above step (4) in the modified silk fibroin mixed solution containing a crosslinking agent in the above step (3) for 60 seconds, taking it out and rotating it in a circular direction at 35°C to form a film at a rotation speed of 60 rpm, completing one immersion treatment; and controlling the surface of the film to remain moist, repeating the immersion treatment 6 times to form the outer layer of the stent coating, thereby obtaining the stent coating, and finally immersing the stent coating in sterile deionized water at 37°C for 1 day to remove unreacted crosslinking agent and silk fibroin molecules to obtain a polyester / silk fibroin composite stent coating.

[0065] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a polyester / silk composite vascular stent coating with a bionic interface, characterized in that: The following steps are involved: (1) degumming silkworm silk with boiling water, sodium carbonate, sodium bicarbonate or biological enzymes to obtain silk fibroin fibers, which are then completely dissolved in a lithium bromide solution to obtain a fibroin solution; pouring the fibroin solution into a dialysis bag, dialyzing with deionized water, filtering to obtain a purified silk fibroin aqueous solution, and evaporating and concentrating the silk fibroin aqueous solution to adjust the concentration of the silk fibroin aqueous solution to 10 to 200 mg / mL; (2) placing the polyester yarn in a sodium carbonate solution for a period of time, washing it with deionized water, completing the degreasing and desizing treatment, repeating the degreasing and desizing treatment several times, and finally obtaining the pretreated polyester yarn; The pretreated polyester yarn is placed in a sodium hydroxide solution for surface activation treatment, and then washed with deionized water to obtain an alkali-treated polyester yarn. (3) Preparation of the inner layer of the stent coating; (a) using the silk fibroin aqueous solution of step (1) as an electrospinning solution, spinning silk fibroin nanofibers on a cylindrical auxiliary rod by electrospinning to obtain an auxiliary rod with silk fibroin nanofibers; the concentration of the silk fibroin aqueous solution is 50-180 mg / mL, the average diameter of the silk fibroin nanofibers is 100-5000 nm, and the average orientation degree of the silk fibroin nanofibers is 30-90%; (b) adding a hydrophilic flexible cross-linking agent to the silk fibroin aqueous solution of step (1) to obtain a modified silk fibroin mixed solution; then dipping the auxiliary rod with silk fibroin nanofibers in the modified silk fibroin mixed solution, taking it out after dipping and placing it in an environment of 20 to 50° C. to rotate and form a film, completing an immersion treatment; repeating the immersion treatment several times to form an inner layer of the stent coating; the silk fibroin concentration in the modified silk fibroin mixed solution is 30 to 100 mg / mL; (4) weaving the polyester yarn treated with alkali in step (2) on the outer surface of the inner layer of the stent coating in step (3) to form a polyester tubular fabric with a weaving angle of 30 to 150 degrees and an axial weaving density of 1 to 20 strands / cm to form a core layer of the vascular stent coating; (5) Immersing the core layer of the vascular stent coating of step (4) in the modified silk fibroin mixed solution prepared in the above step (3), taking it out after immersion and placing it in an environment of 20 to 50° C. for rotation to form a film, thus completing one immersion treatment; repeating the immersion treatment several times to obtain the vascular stent coating; finally, immersing the vascular stent coating in sterile deionized water to remove unreacted crosslinking agent and silk fibroin molecules and dissolve the silk fibroin nanofibers to obtain a polyester / silk fibroin composite vascular stent coating with a bionic interface.

2. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: The concentration of the lithium bromide solution in step (1) is 9.3 M; the dialysis bag is a semipermeable membrane with a molecular weight cutoff of 3 to 50 kDa, and deionized water is used for dialysis for 3 days.

3. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: The mass concentration of the sodium carbonate solution in step (2) is 1%, the temperature of the degreasing and desizing treatment is 95-100° C., and the treatment time is 2 hours; the number of treatments is 2-5 times; the concentration of the sodium hydroxide solution is 20-50 g / L, the surface activation treatment temperature is 30-80° C., and the treatment time is 1-3 hours.

4. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: The cylindrical auxiliary rod in step (3) (a)-(b) is a stainless steel rod with a diameter of 1 to 30 mm.

5. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: In step (3) (a), the rotation speed of the cylindrical auxiliary rod during electrospinning is 100 to 3000 rpm.

6. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: In step (3) (b), the mass ratio of silk fibroin to cross-linking agent is 1.0:(0.3-1.0), the cross-linking agent is polyethylene glycol diglycidyl ether, the immersion time in the modified silk fibroin mixed solution is 10-60 seconds, the immersion treatment is repeated 0-5 times, the rotation speed during rotational film formation is 20-80 rpm, and the rotation direction is along the circumference of the auxiliary rod.

7. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: The polyester yarn in step (4) is any one of polyester monofilament and polyester multifilament, and the specification is 5-200D.

8. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: In step (5), the immersion time in the modified silk fibroin mixed solution is 10 to 60 seconds, the rotation speed during the rotation film formation is 20 to 80 rpm, the rotation direction is along the circumference of the auxiliary rod, and the time is 10 to 30 minutes; the repeated immersion treatment is repeated 2 to 10 times.

9. The method for preparing a polyester / silk composite vascular stent coating with a bionic interface according to claim 1, characterized in that: The temperature of the sterile deionized water in step (5) is 4 to 37° C., and the soaking time is 1 to 3 days.

10. A polyester / silk composite vascular stent coating with a bionic interface prepared according to any one of claims 1 to 9, characterized in that: The modified polyester stent coating is composed of an inner layer, a core layer and an outer layer; the polyester tubular fabric is used as the core layer, and the modified silk nanofiber is used as the inner layer and the outer layer; the modified polyester stent coating has an axial tensile strength of 12.0 MPa and an axial elongation at break of 120%; a circumferential tensile strength of 6.0 MPa and a circumferential elongation at break of 50%; a water bursting strength of 3500 mmHg, a compliance of 10.0% / 100 mmHg, and an overall water leakage of less than 10 mL / min.cm under a water pressure of 120 mmHg 2 , hemolysis rate <0.1%.

Citation Information

Patent Citations

  • A silk fibroin tubular scaffold and its preparation method

    CN102274089A

  • Vascular covered stent with anti-thrombus / anti-tumor function and preparation method thereof

    CN111839811A